Time-Dependence of Stop Marks in Warp-Knitted Fabrics - Christian Hellert; Michael Kieren; Andrea Ehrmann (Tekstilec)
Stop marks are one of the most frequently occurring errors in warp-knitted fabrics. They become visible in a fabric each time a warp-knitting machine stops and restarts. Nevertheless, investigations of such stop marks are rarely found in scientific literature. Here, we report on time-dependent investigations of stop marks in warp-knitted fabrics. Microscopic examination of stop marks after stopping times ranging between 1 s and 7 weeks revealed a superposition of the common stop mark due to imperfectly matching rotational speeds of the warp beam and main shaft, and an additional effect due to relaxation in the machine.